Correlation of single-phase convective heat transfer on spray cooled plain surfaces with high Prandtl number liquids. (July 2023) - Dubil, Konrad; Bender, Jonas; Hoffmann, Felix; Dietrich, Benjamin; Doppelbauer, Martin; Wetzel, Thomas
Highlights: Material properties of binary model fluid representative of transmission oils. Dependence of spray angles on operating conditions must not be neglected. Models for low Prandtl numbers are applicable to high Prandtl numbers. Models for optimal nozzle distances cannot be extrapolated to other distances. Proposed model accounts for variations in nozzle distance and spray coverage. Abstract: Spray cooling with transmission oils is an innovative cooling concept for electrical machines, whereby the coolant wets the end windings directly. The thermal design process of such machines requires reliable correlations of the heat transfer coefficients obtainable. Thereby, the majority of the literature only focuses on low Prandtl number coolants at ideal nozzle distances. The transferability of the existing heat transfer models to highly viscous coolants above and below the optimal nozzle distance has yet to be investigated. Therefore, the heat transfer coefficients of spray cooling on plain surfaces with aqueous glycerol solutions (model fluid) and a transmission oil of type ATF VI was investigated. The model fluid serves the purpose of covering the entire range of material properties of commercial transmission oils with only one liquid. Prandtl numbers ranging from 80 to 340 were investigated. Various cases of spray coverage were researched by varying the nozzle distance ( 2 mm − 100 mm ), the spray angle ( 20 ∘ − 80 ∘ ) and the size of the spray cooled surface ( 6 . 35 × 6 . 35 m m 2 ; 12 . 7 × 12 . 7 m m 2 ). Regarding the case of the optimal nozzle distance, where the spray impact area just inscribes the cooled surface, the experimental data was validated with models from the literature. Large deviations of up to 450% resulted at nozzle distances above and below the optimum. Therefore, a dimensionless correlation of the heat transfer coefficient is proposed which includes all cases of spray coverage investigated, exceeding the applicability range of the existing models. The model describes the experimental data with a mean absolute percentage error of 15%.